Effect of the proper time of nitrogen application on growth, yield and its components of maize plants - Ragab, A. Y.; Ibrahim, M. H. (2009)
Two field experiments were carried out during two successive summer seasons 2001 and 2002 at the experimental Farm, Faculty of Agriculture, Kafr EL Sheikh, Tanta University to find out the proper time to application the recommended dose of nitrogen fertilization [120 kg N/fed] and its effects on growth, yield and its components of maize plants of cultivar [Twe321].1- Application of nitrogen fertilizer in two equal doses [12 at sowing date plus at the first irrigation] gave the best results on dry weight of tassel at age of 80 day in the second season and at age 95 day in the first season, plant height, dry weight of leaves and leaf area/plant at age of 65 day and number of leaves at age of 95 day in the second season and stem diameter at age of 95 day in the first season. 2- Splitting the nitrogen into two equal doses [12 at the first and the second irrigations] significantly increased each of dry weight of stem, number of leaves, stem diameter, total weight ofthe plant at age of 65 day and dry weight of leaves, leaf area/plant at age of 95 day in the second season 3- Splitting the nitrogen into three portions, 1/3 at sowing date, 1/3 at first irrigation and 1/3 at second irrigation caused a significant increase in dry weight of tassel at age of 65 day, total dry weight of plant at age of 80 day, dry weight of ears at age of 95 days in the first season and on number of leaves/plant at age 65 day, dry weight of ears at age of 80 day and plant height, total chlorophyll in leaves, stem diameter, grain yield/fed in ardab and number of leaves/plant at age of95 day in the second season. 4- Dividing the nitrogen into three portions, Y4 at sowing date, 'l1 at first irrigation and Y4 at second irrigation resulted in a significant increase on dry weight of tassel at age of 65 day, dry weight of stem and ears, number of leaves at age of 95 day in the first season.
Includes references.
Summary in Arabic.
1
Keywords: Corn -- Fertilizers -- Economic aspects; Corn -- Yields; Corn -- Weights and measures; Corn -- Growth; Grain -- Yields; Corn Composition; Nitrogen fertilizers -- Physiological effect; Nitrogen fertilizers -- Control